Masterpieces - CAPC (Musée d'Art Contemporain de Bordeaux), Bordeaux (Bordeaux : CAPC Musée d'Art Contemporain de Bordeaux, 2007)
Absalon ; Baquié, Richard ; Barcelo, Miquel ; Becher, Bernd & Hilla ; Billingham, Richard ; Blais, Jean-Charles ; Boisrond, François ; Boltanski, Christian ; Boursier-Mougenot, Céleste ; Breuning, Olaf ; Bulloch, Angela ; Buraglio, Pierre ; Buren, Daniel ; Bustamante, Jean-Marc ; Cattelan, Maurizio ; Combas, Robert ; Convert, Pascal ; Cucchi, Enzo ; Dafflon, Stéphane ; Decrauzat, Philippe ; Delvoye, Wim ; Feyzdjou, Chohreh ; Framis, Alicia ; Fulton, Hamish ; Gilbert & George ; Gillick, Liam ; Goldin, Nan ; Gonzalez-Foerster, Dominique ; Grigely, Joseph ; Halley, Peter ; Hantaï, Simon ; Haring, Keith ; Hirakawa, Noritoshi ; Holzer, Jenny ; Hyber, Fabrice ; Isermann, Jim ; Jugnet, Anne Marie ; Kapoor, Anish ; Kawara, On ; Kelley, Mike ; Kounellis, Jannis ; Laib, Wolfgang ; Lamouroux, Vincent ; Lavier, Bertrand ; Leblon, Guillaume ; Lévêque, Claude ; Levine, Sherrie ; LeWitt, Sol ; Long, Richard ; Majerus, Michel ; Marcel, Didier ; McCarthy, Paul ; Merz, Mario ; Messager, Annette ; Mitchell, Joan ; Molinier, Pierre ; Muntadas, Antoni ; Nauman, Bruce ; Neuhaus, Max ; Oursler, Tony ; Parreno, Philippe ; Peinado, Bruno ; Pierson, Jack ; Raynaud, Jean Pierre ; Readymades belong to everyone ; Rosa, Hervé Di ; Rousse, Georges ; Ruscha, Ed ; Santoro, Vittorio ; Sarkis ; Serra, Richard ; Sicilia, José Maria ; Sparks, Meredyth ; Steinbach, Haim ; Stockholder, Jessica ; Thibeau, Jean-Paul ; Tillmans, Wolfgang ; Toroni, Niele ; Trockel, Rosemarie ; Trouvé, Tatiana ; Vercruysse, Jan ; Viallat, Claude ; Walker, Kelley ; Wearing, Gillian ; Weiner, Lawrence ; Zittel, Andrea
Engels en Frans
boek